Analiss Literasi Informasi dan Motivasi Mahasiswa dalam Penyelesaian Studi di Masa Pandemi COVID-19 - Muhtar Mochamad Solihin (BPSDMP KOMNFO Yogyakarta, Kementerian Komunikasi dan Informatika, 2022)
Students can graduate from their studies on time if they have good information literacy skills and motivation to complete studies even during the COVID-19 pandemic. The aims of this study are to: 1) describe the characteristics of the respondents, and 2) analyze the relationship between information literacy and student motivation in completing studies during the COVID-19 pandemic. This research approach uses quantitative survey method. Data collection techniques by means of observation and distributing online questionnaires to 88 respondents. The sample selection technique used a simple random sampling and the data analysis used descriptive statistics and inferential statistics. The results showed that: 1) almost half of the total respondents (40.91 percent) studied at the Islamic Communication and Broadcasting Study Program (KPI). More than a quarter of the respondents (26.14 percent X 37.50 percent) have a high school (SMA), Madrasah Aliyah (MA) and Islamic boarding school (Ponpes) educational background. The majority of respondents' average pocket money (61.36 percent) is low, ranging from IDR 200,000 to IDR 800,000. The majority of respondents (79.55 percent) are not scholarship recipients, and 2) information literacy has a positive and significant relationship (Sig. 0.000 < 0.05) with student motivation in completing studies during the COVID-19 pandemic. This means that the higher the information literacy competence, the higher the level of student motivation to be able to complete studies on time and vice versa.